Proceedings of the 12th Annual Conference Companion on Genetic and Evolutionary Computation 2010
DOI: 10.1145/1830761.1830858
|View full text |Cite
|
Sign up to set email alerts
|

Automatic summarization of cricket video events using genetic algorithm

Abstract: Sports video mining has gained a lot of popularity in recent years. In this paper, we propose a flexible framework for summarization of cricket video content using genetic algorithm (GA). A summary of a cricket match should contain a variety of events, span the entire duration of the match and contain events of relatively high importance. These three parameters develop into a multi-objective optimization problem that is solved using genetic algorithm. Our experimental results on cricket matches are quite encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Similar studies for sports such as basketball [6], baseball [7], and tennis [8] have also been reported. More recent work, in the domain of sports video summarization, has been reported in [12] and [13] for the game of cricket.…”
Section: A Automatic Highlights Generationmentioning
confidence: 99%
“…Similar studies for sports such as basketball [6], baseball [7], and tennis [8] have also been reported. More recent work, in the domain of sports video summarization, has been reported in [12] and [13] for the game of cricket.…”
Section: A Automatic Highlights Generationmentioning
confidence: 99%